Towards a Theoretical History for Greek Tragedy. (28th April 2015) - Ley, Graham
<x content-type="archive" xml:space="preserve">Abstract</x> Greek tragedy and its theatre have regularly been drawn into modern theoretical formulas about the nature of theatre making, in proposals which have often had their own cause to plead, but which have still been influential on broadly formed views of the theatre in its history. In this essay, Graham Ley argues that much incidental misrepresentation can be found in this kind of writing alongside the occasional remarkable insight, and that the attention given in modern theory to the Greek theatre is generally inadequate. The theorists discussed are Isadora Duncan, Brecht, Boal, and Hans-Thies Lehmann, with examples also taken from performance theory. Ley then goes on to examine what kind of theoretical view of the ancient Greek theatre would be most appropriate today, and offers a vision of it as a dynamic and innovative environment, looking in this second part of the essay at what can be said of early choric tragedy, of the emergence of the actor, and of the innovation of the dramatic scene building. Graham Ley has written essays on various topics over the years for New Theatre Quarterly, but this is his first piece for the journal on his specialist subject, the performance of ancient Greek tragedy.